3‐dimensional metrics of proximal femoral shape deformities in Legg–Calvé–Perthes disease and slipped capital femoral epiphysis. Issue 5 (28th November 2017) - Chan, Elaine F.; Farnsworth, Christine L.; Klisch, Stephen M.; Hosalkar, Harish S.; Sah, Robert L.
ABSTRACT: Legg–Calvé–Perthes disease (LCPD) and slipped capital femoral epiphysis (SCFE) are two common pediatric hip disorders that affect the 3‐dimensional shape and function of the proximal femur. This study applied the principles of continuum mechanics to statistical shape modeling (SSM) and determined 3‐D metrics for the evaluation of shape deformations in normal growth, LCPD, and SCFE. CT scans were obtained from 32 patients with asymptomatic, LCPD, and SCFE hips ((0.5–0.9 mm) 2 in‐plane resolution, 0.63 mm slice thickness). SSM was performed on segmented proximal femoral surfaces, and shape deformations were described by surface displacement, strain, and growth plate angle metrics. Asymptomatic normal femurs underwent coordinated, growth‐associated surface displacements and anisotropic strains that were site‐specific and highest at the greater trochanter. After size‐ and age‐based shape adjustment, LCPD femurs exhibited large displacements and surface strains in the femoral head and neck, with associated changes in femoral head growth plate angles. Mild SCFE femurs had contracted femoral neck surfaces, and surface displacements in all regions tended to increase with severity of slip. The results of this paper provide new 3‐D metrics for characterizing the shape and biomechanics of the proximal femur. Statement of Clinical Significance: Quantitative 3‐D metrics of shape may be useful for understanding and monitoring disease progression, identifying target regions for shape modulation therapies, and objectively evaluating the success of such therapies. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1526–1535, 2018. Abstract : The principles of continuum mechanics were applied to statistical shape modeling to determine displacement and strain metrics in the developing femur. Legg–Calvé–Perthes disease (LCPD) femurs exhibited large displacements and strains in the head and neck relative to the normal asymptomatic femur shape, with associated changes in growth plate angles. Slipped capital femoral epiphysis (SCFE) showed anisotropic strains in the head‐neck junction and greater trochanter. The results of this paper provide new 3‐D metrics for characterizing the shape and biomechanics of the proximal femur.